Profiling of Oral Microbiota in Early Childhood Caries Using Single-Molecule Real-Time Sequencing - Wang, Yuan; Zhang, Jie; Chen, Xi; Jiang, Wen; Wang, Sa; Xu, Lei; Tu, Yan; Zheng, Pei; Wang, Ying; Lin, Xiaolong; Chen, Hui (Frontiers in Microbiology, 2017)
Background: Alterations of oral microbiota are the main cause of the progression of caries. The goal of this study was to characterize the oral microbiota in childhood caries based on single-molecule real-time sequencing. Methods: A total of 21 preschoolers, aged 3–5 years old with severe early childhood caries, and 20 age-matched, caries-free children as controls were recruited. Saliva samples were collected, followed by DNA extraction, Pacbio sequencing, and phylogenetic analyses of the oral microbial communities. Results: Eight hundred and seventy six species derived from 13 known bacterial phyla and 110 genera were detected from 41 children using Pacbio sequencing. At the species level, 38 species, including Veillonella spp., Streptococcus spp., Prevotella spp., and Lactobacillus spp., showed higher abundance in the caries group compared to the caries-free group (p < 0.05). The core microbiota at the genus and species levels was more stable in the caries-free micro-ecological niche. At follow-up, oral examinations 6 months after sample collection, development of new dental caries was observed in 5 children (the transitional group) among the 21 caries free children. Compared with the caries-free children, in the transitional and caries groups, 6 species, which were more abundant in the caries-free group, exhibited a relatively low abundance in both the caries group and the transitional group (p < 0.05). We conclude that Abiotrophia spp., Neisseria spp., and Veillonella spp., might be associated with healthy oral microbial ecosystem. Prevotella spp., Lactobacillus spp., Dialister spp., and Filifactor spp. may be related to the pathogenesis and progression of dental caries.